MEMBANGUN SISTEM INFORMASI PENGELOLAHAN DATA NASABAH BERBASIS WEB DI BANK SAMPAH SAMAWA - Erwin Mardinat; Saiful Khair (Universitas Bumigora, 2017)
The purpose of this research is to build information system of customer data management at Samawa garbage bank. Institute of Cooperation founded by the community as a place of trash collection that has been sorted, the process of customer transactions still apply manual system recording all customer transactions using a cooperative ledger. It causes the bank officials intricate in managing the data and somehow the data continue to increase. The solution of the problems that are happening in Samawa Waste Bank is the application of information technology that is to put up an information system or relevance allowing officers to handle customer data. This research is built using PHP programming language by operating codeigniter framework and MySQL as its database. The method in the construction of this system is the waterfall model. The results of the research are able to be used in the process of controlling clients’ data on cooperative institutions thus to accelerate the process of customer statistics management.